Utilizing Instagram Accounts for Business as a Tourism Marketing Communication Strategy in the New Normal Period - Yenny Aspriyaningsih; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2022)
This study examines how to use Instagram as a tourism strategy marketing communication in new normal period at the Hawai Waterpark Malang. In this study, used an analytical in the form of a tourism marketing communication strategy theory (elements marketing mix) utilizing the features that exist on Instagram for business. The purpose of this study was to determine whether the use of Instagram accounts can help tourism marketing communication. This research uses descriptive qualitative methods. The datas are collected by documentation, observation and interviews with the managers of Hawai Waterpark Malang. The results of the study show that the use of Instagram accounts as a tourism marketing communication strategy during the New Normal is very helpful for marketing communication activities. The features offered by Instagram business make the marketing communication process more efficient. Instagram carries of information between Hawai Waterpark Malang and consumers who will visit Hawai Waterpark Malang.